Determination of Benthic Macroinvertebrate Fauna and Some Physicochemical Properties of Balaban Lake (Menderes- Izmir) - Alperen Ertaş; Tuğba Boz; İnci Tüney Kızılkaya (Aquatic Sciences and Engineering, 2021)
In this study, we aimed to identify the benthic macroinvertebrate fauna and some physicochemical characteristics of Balaban Lake located in Menderes, Izmir. For this, benthic macroinvertebrate and water samples were taken from 5 stations of the lake from October 2019 to August 2020. As a re-sult, a total of 25 taxa were identified and were classified as Annelida (Oligochaeta and Hirudinea), Mollusca (Bivalvia and Gastropoda), Crustacea and other Insecta (Trichoptera, Coleoptera and Dip-tera). The sampling stations were clustered by using the Bray-Curtis UPGMA analysis in terms of the distribution of the benthic macroinvertebrates. As a result of the UPGMA analysis, the 2nd and 3rdstations(88%)werethemostsimilartoeachother.Thesecondmostsimilarstationstoeachother were determined as the 1st and 4th stations (75%). This situation can be explained by the bot-tom structure (rich vegetation) of these stations. According to Pearson Correlation, there is a strong positivecorrelation(p lt;0.01)ofTU,EC,TDSandTPwithNaiscommunis,whilethereisstrongpositive correlation (p lt;0.05) of TU, EC and TDS with Nais elinguis. On the other hand, there is a strong negative correlation (p lt;0.01) of TU, pH, EC, TDS and TP with Gammarus sp. This study is the firststudyfordeterminingBalabanLakebenthicfauna.That’swhyallthetaxadiagnosedinthestream has been recorded for the first time.